Identification, gene expression and genetic polymorphism of zinc finger A20/AN1 stress-associated genes, HvSAP, in salt stressed barley from Kazakhstan - Baidyussen, Akmaral; Aldammas, Maryam; Kurishbayev, Akhylbek; Myrzabaeva, Malika; Zhubatkanov, Askar; Sereda, Grigory; Porkhun, Raisa; Sereda, Sergey; Jatayev, Satyvaldy; Langridge, Peter; Schramm, Carly; Jenkins, Colin L. D.; et al. (BMC plant biology, 2020)
A family of genes designated as the Zinc finger A20/AN1 Transcription factors encoding stress-associated proteins (SAP) are well described in Arabidopsis and rice, and include 14 AtSAP and 18 OsSAP genes that are associated with variable tolerances to multiple abiotic stresses. The SAP gene family displays a great diversity in its structure and across different plant species. The aim of this study was to identify all HvSAP genes in barley (Hordeum vulgare L.), to analyse the expression of selected genes in response to salinity in barley leaves and develop SNP marker for HvSAP12 to evaluate the association between genotypes of barley plants and their grain yield in field trials. In our study, 17 HvSAP genes were identified in barley, which were strongly homologous to rice genes. Five genes, HvSAP5, HvSAP6, HvSAP11, HvSAP12 and HvSAP15, were found to be highly expressed in leaves of barley plants in response to salt stress in hydroponics compared to controls, using both semi-quantitative RT-PCR and qPCR analyses. The Amplifluor-like SNP marker KATU-B30 was developed and used for HvSAP12 genotyping. A strong association (R = 0.85) was found between KATU-B30 and grain yield production per plant of 50 F breeding lines originating from the cross Granal × Baisheshek in field trials with drought and low to moderate salinity in Northern and Central Kazakhstan. A group of HvSAP genes, and HvSAP12 in particular, play an important role in the tolerance of barley plants to salinity and drought, and is associated with higher grain yield in field trials. Marker-assisted selection with SNP marker KATU-B30 can be applied in barley breeding to improve grain yield production under conditions of abiotic stress.